Stability current for single-phase grid-connected photovoltaic systems - Truong , Viet Anh; Nguyen, Ba Thuan (Journal of Technical Education Science, 2010)
This paper presents a single-phase, grid-connected solar power system. The main characteristic of the model is that sine waves of the power grid is used as controlling waves in the modulation, allowing the frequency and voltage monitoring of the power grid. Then the voltage fluctuation of the solar energy to the power grid to stabilize the current is put into consideration. Experimental results on the model have revealed that the ability to stabilize current injected into grid is good, regardless of the changes of voltage and frequency on the grid or on the DC voltage of the inverter system. Additionally, the model has the ability to reduce the transmission of reactive power to grid to improve work efficiency of the electronic switching in inverters during the transmision of active power.